Photography and Catastrophe: Reading Photographs of the Disaster Event - Zaki Habibi (Jurnal Komunikasi, 2011)
This article analyses 24 selected photographs—organized into two photo series—about one particular catastrophic event: the impacts of Merapi Volcano’s eruption in Java, Indonesia, on October to November 2010. These photographs are made by two different groups of profession, professional photojournalists and volunteers, who worked in relatively same locations during the post-eruption. The analytical methods are informed by Roland Barthes’ thought on semiotics as well as critical theories in visual media specifically photography. This critical reading leads me to found distinctive representations constructed by each photo series. There are three elements that create this kind of representations, they are the relation of subject-object, visual codes, and visual perception. The first photo series made by professional photojournalists represent disaster event as a paradox: between “destruction” and “beauty” of the nature. Meanwhile, the photo series photographed by volunteers more focus on representation of the survivors in rehabilitating their lives. All these findings result in the conclusion that shows the role of photography—on perception and memory construction regarding time, space, body and mind—is exceedingly relative, particularly relating to catastrophe and disaster.